2017
DOI: 10.14744/nci.2017.88598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic regimens in total knee artroplasty, retrospective study

Abstract: OBJECTIVE:Analgesic therapies have an immense role in early rehabilitation period after total knee arthroplasty (TKA) and multimodal approaches should be considered as the first choice of treatment. In this retrospective study, the aim was to evaluate the effectiveness of multimodal analgesic therapies for TKA, including femoral nerve block (FNB) and patient controlled analgesia (PCA).METHODS:The data of 79 patients who underwent TKA between January and December 2016 were retrospectively evaluated. In all, 63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(27 reference statements)
1
0
0
Order By: Relevance
“…Reduction in the pain intensity, judged according to the lower scores on the NPS in comparison with the opioid group, found in the FNB group was in accordance with the results of several other clinical trials. [29][30][31][32][33][34][35][36] Publications on the postoperative efficacy of FICNB are less abundant, but a meta-analysis unequivocally confirms the results of the present study. 37 One of the rare available clinical studies publishing the head-tohead comparison between 3-in-1 FNB and FIC-NB found no difference in the efficacy and safety of these two multi-modal analgesic techniques, 34 corroborating thus the current results.…”
Section: Mp -Morphine Paracetamol Fnb -Femoral Nerve Block Ficnb -Fsupporting
confidence: 82%
“…Reduction in the pain intensity, judged according to the lower scores on the NPS in comparison with the opioid group, found in the FNB group was in accordance with the results of several other clinical trials. [29][30][31][32][33][34][35][36] Publications on the postoperative efficacy of FICNB are less abundant, but a meta-analysis unequivocally confirms the results of the present study. 37 One of the rare available clinical studies publishing the head-tohead comparison between 3-in-1 FNB and FIC-NB found no difference in the efficacy and safety of these two multi-modal analgesic techniques, 34 corroborating thus the current results.…”
Section: Mp -Morphine Paracetamol Fnb -Femoral Nerve Block Ficnb -Fsupporting
confidence: 82%